MODELING FERTILITY RATE OF INDONESIA IN THE PRESENCE OF INTERFERENCE: THE 2004 TSUNAMI. - Akoth, Odero Everlyne; Onyango, Fredrick O.; Otumba, Edgar O. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
A lot of studies have been done on fertility for many years. But, scarce literature is found onmodeling of fertility in the presence of interference, yet interference to fertility is a commonphenomenon. This study focused on modeling of fertility rate in the presence of interference. Wehave fitted Probability distributions to interference free data set of Indonesia 2002 and also to theIndonesia 2007 fertility data set which had interference in it, so as to determine the effect ofinterference on the shape of the fertility data. The parameter of the distributions were estimatedand then fitted by maximum likelihood estimation available in the `fitdistr' package, in the Rstatistical software. The model life table approach was also used to determine the net fertilityvalue F0 which was modeled from the net reproduction value R0. A relationship between fertilityrate in the presence of interference and population growth was then established. A major findingof this study is that interference free fertility data fit a gamma distribution, data containinginterference fit a modified gamma distribution with a mounded but skewed shape. The resultsalso showed that in the presence of interference F0 >2, hence population increases. Results of thisstudy would help demographers and businessmen to deal with random factors that affect all areasof demography and businesses striving to succeed in today's highly competitive environment.Probability distribution is a scientific tool that would help demographers and business persons todeal with uncertainty and hence make informed decisions. The modeling results would protectdemographers from potential time and money loss which might arise due to invalid modelselection thereby, helping the Government in planning for social amenities for its citizens.